2014
DOI: 10.1080/11250003.2014.977359
|View full text |Cite
|
Sign up to set email alerts
|

Vasculature-guided neural migration in mouse cerebellum

Abstract: Neural migration is regarded as a key step for cortical development and cortical lamination. While classical theory holds that immature neurons migrate to their destinations along radial glia, there is some preliminary evidence showing that vasculature is probably involved in that process as well. In this study, we compared vascular development with that of radial glia and the migration of neurons, so that the relationships among them could be elucidated. We found that the radial glial cells and vasculature we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Neurotoxicity is the one of main Veratru m alkaloid's toxicities . Our previous work demonstrated that veratramine ( 7 ) and 12 β ‐hydroxyveratroylzygadenine ( 9 ) can access to brain tissue through the blood‐brain barrier to cause oxidative stress and consequently lead to DNA damage in mouse cerebellum and cerebral cortex; besides, it also raises the expression of Ogg1 mRNA as a compensatory adjustment to the antioxidant defense status and DNA repair systems . Moreover, jervine ( 8 ), germerine ( 10 ) and neogermbudine ( 11 ) were also confirmed to induce various degrees of oxidative DNA damage in the cerebellum and the cerebral cortex of mice …”
Section: Introductionmentioning
confidence: 97%
“…Neurotoxicity is the one of main Veratru m alkaloid's toxicities . Our previous work demonstrated that veratramine ( 7 ) and 12 β ‐hydroxyveratroylzygadenine ( 9 ) can access to brain tissue through the blood‐brain barrier to cause oxidative stress and consequently lead to DNA damage in mouse cerebellum and cerebral cortex; besides, it also raises the expression of Ogg1 mRNA as a compensatory adjustment to the antioxidant defense status and DNA repair systems . Moreover, jervine ( 8 ), germerine ( 10 ) and neogermbudine ( 11 ) were also confirmed to induce various degrees of oxidative DNA damage in the cerebellum and the cerebral cortex of mice …”
Section: Introductionmentioning
confidence: 97%